The Influence of Competence, Training, and Career Development on Employee Performance at Pabrik Gula Lestari Nganjuk Installation Section - Kusnayanti, Fitri; Rini, Hesty Prima (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Performance is a measure of the company's goals and the comparison of the work of an employee to the company's standards. This study aims to determine the effect of competency, training, and career development on the performance of PG Lestari employees in the Installation Section. Motede's research uses quantitative research meteodes and sampling techniques are nonprobability sampling with purposive sampling techniques. The measuring scale used is the likert scale 1-4. The sample of this study was 39 people in the Installation section of the Lestari Nganjuk Sugar Factory with the stipulation that only employees have the status of permanent employees and have attended training at least once. Data processing and hypothesis testing using Partial Least Square (PLS) assistance. The results of this study were 1) employee competency (X1) had no significant effect on employee performance (Y), 2) employee training (X2) had a significant effect on employee performance (Y), and 3) employee career development (X3) had a significant effect on employee performance (Y).